Probing understanding: emergent second language readers’ visual literacy / Marina Binti Mohd Arif - Marina, Mohd Arif (2012)
Due to the visually saturated world we live in more children are becoming visual learners but the school curriculum is yet to acknowledge this change and a lot of literacy teaching still focuses on the ability to decode and encode printed words. There is a need then to look into the potential of visuals in the teaching of second language literacy and to acknowledge the individual differences and needs of young learners. This study was conducted to better understand emergent second language readers’ visual literacy by looking at the meaning-making process that children engage in when transacting with books that consist of textual as well as visual input. Six 7-year old emergent second language readers were selected as the participants of the study and they went through individual sessions with the researcher using four types of picture books – printed picture book, wordless picture book, comic and online picture book. In the individual sessions, the young learners’ interpretations of visuals and how they use visuals to interpret the words as well the story in the picture books were documented through observation, interview, video and audio recording. Data from these sources were analyzed using the constant comparative method. They were analyzed for emerging themes which were used to develop categories for tentative hypotheses that became the basis for explaining the data’s meaning.